(untitled) (Research, Society and Development, 2022)
The economic, political and institutional crisis in Brazil, experienced since 2014, fostered a change in labor law. The Labor Reform, Law nº 13.467/2017, introduced, modified and revoked a series of provisions in the Consolidation of Labor Laws. Among the most relevant provisions, article 611-A deals with the prevalence of the negotiated over the legislated. The new article raised doubts not only about its constitutionality, but also about the limits of the Collective Bargaining Agreement and Convention, making it essential to investigate these issues. To obtain the desired conclusions, this work sought the position of the Federal Supreme Court on the matter, as well as the doctrinal positions. In this way, the work uses a qualitative methodology that, through a bibliographic review, induces an answer to the problem. It is concluded that the position of the Federal Supreme Court is for the constitutionality of what is negotiated over what is legislated, restricting the normative power of negotiations only when they are confronted with labor parties of absolute unavailability.